2011
DOI: 10.1007/s10735-011-9323-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage is a preliminary step during rat tongue carcinogenesis induced by 4-nitroquinoline 1-oxide

Abstract: The aim of this study was to investigate oxidative DNA damage during 4-nitroquinoline 1-oxide (4NQO)-induced rat tongue carcinogenesis. For this purpose, male Wistar rats were distributed into three groups of 10 animals each and treated with 50 ppm 4NQO solution through their drinking water for 4, 12, and 20 weeks. Ten animals were used as negative control. The alkaline Comet assay modified with lesion-specific enzymes was used to detect single and double strand breaks, labile sites (SBs), and oxidised purines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Therefore, we chose 4NQO model to further investigate these effects in vivo. Oxidative DNA damage is a preliminary step during rat tongue carcinogenesis induced by 4NQO (26). Kohda and colleagues concluded that the 8-OHdG, which was regarded as a major marker of DNA oxidative damage (27,28), can be attributed to 4HAQO-DNA adducts in 4NQO animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we chose 4NQO model to further investigate these effects in vivo. Oxidative DNA damage is a preliminary step during rat tongue carcinogenesis induced by 4NQO (26). Kohda and colleagues concluded that the 8-OHdG, which was regarded as a major marker of DNA oxidative damage (27,28), can be attributed to 4HAQO-DNA adducts in 4NQO animal model.…”
Section: Discussionmentioning
confidence: 99%
“…In several types of MPS, previous studies conduced by our research group have revealed changes in biomarkers of oxidative stress, demonstrating lipid peroxidation and protein oxidation, as well as alterations in erythrocyte antioxidant enzymes (Pereira et al 2008(Pereira et al , 2010, suggesting, therefore a possible involvement of reactive oxygen species in these disorders. Intralysosomal GAGs accumulation, directly or indirectly, may cause oxidative imbalance as far as increased cancer risk (Filippon et al 2011b;Miranda et al 2011). We assume that MPS I is able to induce genetic damage in peripheral blood cells as a result of oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…The medium-term assay is based on the multi-step process of carcinogenesis characterized by initiation, promotion and tumor progression. Chronic administration of 4-NQO in drinking water simulates rat tongue carcinogenesis that mimics the human condition, thus providing an ideal model for studying tumor pathobiology (Ribeiro et al 2004;Miranda et al 2011).…”
Section: W Limmentioning
confidence: 99%